Antioxidant Supplementation for Erectile Dysfunction: Systematic Review and Meta-Analysis of Double-Blind, Randomized, Placebo-Controlled Trials - Ranjith Ramasamy; Samir Bhattacharyya; Taylor P. Kohn; Larry E. Miller (The World Journal of Men's Health)
Purpose: This meta-analysis aimed to determine the efficacy and safety of antioxidant supplementation for treating erectile dysfunction (ED). Materials and Methods: We systematically searched MEDLINE, Embase, and the Cochrane Library for double-blind, randomized, placebo-controlled trials of oral antioxidant supplementation in men with ED. Erectile function was assessed by the International Index of Erectile Function-Erectile Function domain (IIEF-EF) score. Using random-effects meta-analysis models, antioxidant and placebo groups were compared for erectile function using the mean difference in IIEF-EF score adjusted to a 6–30 scale and for side effects using the log risk ratio. Results: The review included 23 trials of 1,583 men (median age 51 years) treated with antioxidant supplementation or placebo for a median of 12 weeks (range, 4 weeks to 6 months). Antioxidant supplementation significantly improved erectile function compared to placebo, with a mean difference of 5.5 points (95% confidence interval [CI]: 3.7 to 7.3; p<0.001) on the IIEF-EF. In meta-regression, the treatment benefit was greater in men with more severe ED (p<0.001). Side effects were uncommon, none were serious, and the frequency was comparable between antioxidant (3.8%) and placebo (2.1%) groups (log risk ratio=0.36; 95% CI: -0.24 to 0.97; p=0.24). Conclusions: Antioxidant supplementation appears safe and significantly improves erectile function in men with ED, particularly those with more severe symptoms. Limitations of this review included unknown long-term efficacy and safety and the inability to make specific product and dosing recommendations due to the variety of antioxidants and regimens studied.